Long-Term Outcomes of IgG4-Related Ophthalmic Disease in a Chinese IgG4-Related Disease Cohort - Gan, Linyang; Luo, Xuan; Fei, Yunyun; Peng, Linyi; Zhou, Jiaxin; Li, Jieqiong; Lu, Hui; Liu, Zheng; Zhang, Panpan; Liu, Xiaowei; Zhang, Wen (Frontiers in Medicine, 2021)
Purpose: to define the treatment response and long-term outcomes of a large IgG4-related ophthalmic disease (IgG4-ROD) cohort. Methods: 132 patients with a minimal follow-up of one year were included in this study. Demographic, clinical and laboratory data were collected. Treatment response was assessed by the IgG4-RD responder index (IgG4-RD RI). Risk factors for relapse were analyzed with Cox regression analysis. Results: The median follow-up time was 39 months. Lacrimal gland involvement was detected in 87.9% cases. Extraocular muscles, trigeminal nerve and other soft tissue were affected in 25.8%, 6.1% and 18.2% patients. 122 patients received glucocorticoids-based therapy. Median glucocorticoids therapy duration was 33 months. Out of 125 patients with immunosuppressant therapy, 76 (60.8%) patients received more than one class of immunosuppressant. At 6th month, median IgG4-RD RI declined from 12 to 1 and 105 (79.5%) patients achieved complete response (CR). Relapse occurred in 49 (37.1%) patients. Multivariate Cox regression analysis exhibited CR at 6th month and prompt glucocorticoids therapy were independent protective factors for relapse. Patients with multiple ocular lesions suffered a higher risk of relapse. No patient had severe adverse reactions to the treatment in this study. Conclusion: Relapse was common in patients with IgG4-ROD. Relapsed and non-relapse patients shared similar demographic features, baseline clinical characteristics and laboratory findings. Multiple ocular lesions involvement was associated with a higher risk of relapse. CR at 6th month might be a predictor for better prognosis in IgG4-ROD. Thus, more aggressive regimen should be prescribed for patients with poor initial response.